Deciphering the Molecular Signatures Associated With Resistance to Botrytis cinerea in Strawberry Flower by Comparative and Dynamic Transcriptome Analysis - Xiao, Guilin; Zhang, Qinghua; Zeng, Xiangguo; Chen, Xiyang; Liu, Sijia; Han, Yongchao (Frontiers in Plant Science, 2022)
Gray mold caused by Botrytis cinerea, which is considered to be the second most destructive necrotrophic fungus, leads to major economic losses in strawberry (Fragaria × ananassa) production. B. cinerea preferentially infects strawberry flowers and fruits, leading to flower blight and fruit rot. Compared with those of the fruit, the mechanisms of flower defense against B. cinerea remain largely unexplored. Therefore, in this study, we aimed to unveil the resistance mechanisms of strawberry flower through dynamic and comparative transcriptome analysis with resistant and susceptible strawberry cultivars. Our experimental data suggest that resistance to B. cinerea in the strawberry flower is probably regulated at the transcriptome level during the early stages of infection and strawberry flower has highly complex and dynamic regulatory networks controlling a multi-layered defense response to B. cinerea. First of all, the higher expression of disease-resistance genes but lower expression of cell wall degrading enzymes and peroxidases leads to higher resistance to B. cinerea in the resistant cultivar. Interestingly, CPKs, RBOHDs, CNGCs, and CMLs comprised a calcium signaling pathway especially play a crucial role in enhancing resistance by increasing their expression. Besides, six types of phytohormones forming a complex regulatory network mediated flower resistance, especially JA and auxin. Finally, the genes involved in the phenylpropanoid and amino acids biosynthesis pathways were gene sets specially expressed or different expression genes, both of them contribute to the flower resistance to B. cinerea. These data provide the foundation for a better understanding of strawberry gray mold, along with detailed genetic information and resistant materials to enable genetic improvement of strawberry plant resistance to gray mold.